Hydroxytyrosol Inhibits Cannabinoid CB1 Receptor Gene Expression in 3T3‐L1 Preadipocyte Cell Line. Issue 2 (February 2016) - Tutino, Valeria; Orlando, Antonella; Russo, Francesco; Notarnicola, Maria
<x xml:space="preserve">Abstract</x> The 3T3‐L1 preadipocyte cell line is a well characterized cell model for studying the adipocyte status and the molecular mechanisms involved in differentiation of these cells. 3T3‐L1 preadipocytes have the ability to synthesize and degrade endocannabinoid anandamide (AEA) and their differentiation into adipocytes increases the expression of cannabinoid (CB1) and PPAR‐γ receptors. Clinically, the blocking stimulation of the endocannabinoid pathway has been one of the first approaches proposed to counteract the obesity and obesity‐associated diseases (such as diabetes, metabolic syndrome and cancer). In this connection, here we studied in cultured 3T3‐L1 pre‐adipocytes the effects of n‐3‐PUFA, α‐Linolenic acid (OM‐3), n‐6‐PUFA, Linoleic acid (OM‐6), and hydroxytyrosol (HT) on the expression of CB1 receptor gene and the adipogenesis‐related genes PPAR‐γ, Fatty Acid Synthase (FAS) and Lipoprotein Lipase (LPL). HT was able to inhibit 3T3‐L1 cell differentiation by down‐regulating cell proliferation and CB1 receptor gene expression. HT exhibited anti‐adipogenic effects, whereas OM‐3 and OM‐6 exerted an inhibitory action on cell proliferation associated with an induction of the preadipocytes differentiation and CB1 receptor gene expression. Moreover, the expression of FAS and LPL genes resulted increased after treatment with both HT and OM‐3 and OM‐6. The present study points out that the intake of molecules such as HT, contained in extra virgin olive oil, may be considered also in view of antiobesity and antineoplastic properties by acting directly on the adipose tissue and modulating CB1 receptor gene transcription. J. Cell. Physiol. 231: 483–489, 2016. © 2015 Wiley Periodicals, Inc.